"She will control my son": Navigating womanhood, English and social mobility in India. (4th May 2022) - Highet, Katy
Abstract: Through its colonial, class‐ and caste‐based history, English in India has come to be seen as a powerful resource that opens doors for those who 'have' it and holds back those who do not. For women, English ostensibly offers various promises in addition to employment: progressiveness and 'empowerment'; and the potential for upward mobility through marriage. Yet, the conversion of English capital for English‐speaking Indian women proves to be intensely complex in practice, as many find themselves forced to navigate between shifting moral regimes attached to 'tradition' and 'modernity'. Drawing on ethnographic fieldwork in an NGO in Delhi that offers free English training to 'disadvantaged youth', this paper explores how English capital is managed by young women striving to attain middle classness through English, and how their class, caste and gender positionings are negotiated across particular time‐space configurations as they seek to become English speakers. सारांश: भारत में अपने उपनिवेश, वर्ग और वर्ण पर आधारित इतिहास के द्वारा अंग्रेजी एक प्रभावशाली संसाधन के रूप में देखी जाती है। एक ऐसा संसाधन जिसे प्राप्त करने पर दरवाज़े खुल सकते हैं, और जिसे न प्राप्त करने पर प्रगति कठिन है । महिलाओं के लिए अंग्रेजी जाहिरा तौर पर नौकरी के अतिरिक्त प्रगति एवं सशक्तिकरण की संभावना पेश करती है। तथा विवाह के द्वारा सामाजिक गतिशीलता की संभावना पेश करती है। परन्तु व्यव्हार में महिलाओं के लिए इस पूँजी का परिवर्तन अत्यंत जटिल है। अनेक महिलाएँ परंपरा और आधुनिकता की लगातार बदलती हुई नैतिक नीतिओ का संचालन करने पे मजबूर होती हैं। यह लेख दिल्ली के एक मुफ्त में अंग्रेजी पढ़ाने वाले NGO में किए हुए नृवंशविज्ञानिक अनुसंधान पर आधारित है। अंग्रेजी भाषी बनके सामाजिक गतिशीलता पामने का प्रयास करने वाली यह युवा महिलाऐं कैसे समय और स्थल के अनुसार अपने वर्ग, वर्ण, एवं लिंग का मोलभाव करती हैं, इसका बयान करता है।